ENHANCING CLIMATE RESILIENCE FOR A SUSTAINABLE FUTURE: A REVIEW - Dr. Anil Kumar, Rishav Raj (Redshine Archive, 2024)
Climate resilience stands as a cornerstone in the pursuit of a sustainable future amidst the intensifying threats posed by environmental upheavals. This review paper critically examines diverse pathways aimed at bolstering resilience, with a particular focus on interdisciplinary strategies, community involvement, and the integration of innovative technologies. Through a comprehensive analysis of existing literature, this paper highlights the significance of amalgamating climate adaptation measures with social, economic, and environmental endeavors to fortify resilience both locally and globally. Furthermore, it underscores the pivotal role of renewable energy adoption, ecosystem preservation, and the establishment of equitable policy frameworks in mitigating the adverse effects of climate change. By synthesizing current knowledge and identifying gaps in research, this review aims to provide valuable insights and recommendations for fostering a more resilient and prosperous future for all.